1998
DOI: 10.1128/jvi.72.1.273-278.1998
|View full text |Cite
|
Sign up to set email alerts
|

An Avirulent Mutant of Rabies Virus Is Unable To Infect Motoneurons In Vivo and In Vitro

Abstract: An antigenic double mutant of rabies virus (challenge virus standard [CVS] strain) was selected by successive use of two neutralizing antiglycoprotein monoclonal antibodies, both specific for antigenic site III. This mutant differed from the original virus strain by two amino acid substitutions in the ectodomain of the glycoprotein. The lysine in position 330 and the arginine in position 333 were replaced by asparagine and methionine, respectively. This double mutant was not pathogenic for adult mice. When inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 31 publications
0
36
0
3
Order By: Relevance
“…Mar mutants of MHV, Ross River virus, rabies virus, and Venezuelan equine encephalitis virus became less virulent than their parent strains (Coulon et al, 1998;Johnson et al, 1990;Vrati et al, 1996;Wang et al, 1992). However, the virulence of mar mutant virus of FIPV in cats remains unexamined.…”
Section: Discussionmentioning
confidence: 99%
“…Mar mutants of MHV, Ross River virus, rabies virus, and Venezuelan equine encephalitis virus became less virulent than their parent strains (Coulon et al, 1998;Johnson et al, 1990;Vrati et al, 1996;Wang et al, 1992). However, the virulence of mar mutant virus of FIPV in cats remains unexamined.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments showed that the double mutant was able to infect BHK cells, neuroblastoma cells, and freshly prepared embryonic motoneurons, albeit with a lower efficiency than the parental strain CVS. Upon further incubation at 37 C, the motoneurons became resistant to infection by the mutant while remaining permissive to infection by the CVS strain (Coulon et al, 1998). Thus, rabies virus can use different types of receptors: a molecule that is expressed ubiquitously at the surface of continuous cell lines and that is recognized by both CVS and the double mutant and a neuron-specific molecule that is not recognized by the double mutant.…”
Section: Sindbis Virusmentioning
confidence: 99%
“…28 To further increase the safety profile of the vector, an arginine to glutamic acid mutation was introduced at amino acid position 333 of RABV G, which greatly reduces neurovirulence. 23,29,30 To develop full-length NIPARAB cDNA for use in recovery of the recombinant virus, we inserted a codon-optimized version of NiV G (Bangladesh strain) into the BNSP333 vector in between RABV N and P genes. This cDNA serves as the antigenome template from which single-stranded negative-sense RNA genomes are made.…”
Section: Rescue Of Niparab In Cell Culturementioning
confidence: 99%